Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/02619768.2018.1448777
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers’ proactive strategies for avoiding study-related burnout during teacher education

Abstract: The study aims to gain a better understanding of the function of proactive strategies in buffering study burnout among student teachers at the early stage of their studies. There is some evidence that the use of active social coping strategies during studies is related to reduced burnout levels among early career teachers. Less is known about the association between the proactive strategies and burnout among student teachers. Altogether, 244 Finnish student teachers completed the survey.The data were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 81 publications
3
56
0
7
Order By: Relevance
“…There is also evidence that time management (goal setting, prioritizing, and planning) is an effective strategy in reducing burnout risk among teachers (Peeters and Rutte 2005). We recently showed that the proactive strategy use was associated with the reduced risk of student teacher burnout, particularly in terms of exhaustion and inadequacy being experienced (Väisänen et al 2018). Proactive self-regulation has also been found to be related to lower risk of burnout among school principals .…”
Section: Proactive Strategies For Reducing Burnoutmentioning
confidence: 90%
See 2 more Smart Citations
“…There is also evidence that time management (goal setting, prioritizing, and planning) is an effective strategy in reducing burnout risk among teachers (Peeters and Rutte 2005). We recently showed that the proactive strategy use was associated with the reduced risk of student teacher burnout, particularly in terms of exhaustion and inadequacy being experienced (Väisänen et al 2018). Proactive self-regulation has also been found to be related to lower risk of burnout among school principals .…”
Section: Proactive Strategies For Reducing Burnoutmentioning
confidence: 90%
“…H3: Proactive strategy use is likely to be associated with reduced burnout risk (Pietarinen et al 2013a. However, the function of self-and co-regulative strategies in reducing experienced socio-contextual burnout varies ,Väisänen et al 2018 across the profiles.…”
Section: Aim Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to study-related burnout among student teachers, Väisänen et al (2018) found that coping strategies including efforts to manage stress reduced study-related burnout. Even though levels of burnout are low among student teachers, burnout as a concept is widely acknowledged at schools as being an important issue to deal with.…”
Section: Burnout Among Student Teachersmentioning
confidence: 99%
“…Proactive strategies have a positive and forwardlooking approach to managing classroom interaction and dealing with problematic teacher-pupil encounters (Clunies-Ross et al 2008;Greenglass and Fiksenbaum 2009). It has been shown that student teachers' proactive strategies are related to decreased burnout and suggested that learning of proactive classroom strategies should be facilitated throughout the Finnish teacher education programmes (Pietarinen et al 2013;Väisänen et al Forthcoming). Furthermore, student teachers with more education employ more proactive strategies than student teachers with less training do (Woodcock and Reupert 2013).…”
Section: Student Teachers' Proactive and Reactive Strategiesmentioning
confidence: 99%